Development of Interactive Learning Media for Basic Concepts of 3D Objects - M. Ramadhani; Dina Afriani (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2025)
The problem that occurs in class XI Multimedia at SMK Negeri 1 Gambut is the lack of enthusiasm and student participation in 2D and 3D Animation Engineering subjects. To answer this problem, interactive learning media was created using Articulate Storyline 360 with a focus on Basic Concepts of 3D Objects, to provide learning material more interesting and accesssible form, especially for students who have difficulty with abstract visualization in conventional learning. Simultaneously with the development process, a feasibility review was also carried out to determine whether the media was feasible for use in classroom learning. The method used is Research and Development (R&D) with the Borg and Gall model, which has been modified into five stages: (1) preliminary study, (2) planning, (3) initial product development, (4) testing and evaluation, and (5) final product and distribution. The feasibility test of the media was conducted through: content validation by two content experts, media validation by two media experts, individual trial by students, and field trials evaluation by students. The final results of the research indicate that the developed media can be accessed offline through Android and Windows devices. The validation results indicated that the material expert scored 4.59 and the media expert scored 4.85, both categorized as very good. The individual trial and field trial resulted in scores of 4.20 and 4.64, respectively, both categorized as very good. Based on the results, the learning media was declared feasible for use in learning 3D object material in vocational schools.